Interstrain differences in chronic hepatitis and tumor development in a murine model of inflammation‐mediated hepatocarcinogenesis12. Issue 1 (27th May 2013) - Potikha, Tamara; Stoyanov, Evgeniy; Pappo, Orit; Frolov, Antonina; Mizrahi, Lina; Olam, Deborah; Shnitzer‐Perlman, Temima; Weiss, Ido; Barashi, Neta; Peled, Amnon; Sass, Gabriele; Tiegs, Gisa; et al.
Abstract Chronic inflammation is strongly associated with an increased risk for hepatocellular carcinoma (HCC) development. The multidrug resistance 2 (Mdr2)–knockout (KO) mouse (adenosine triphosphate–binding cassette b4−/−), a model of inflammation‐mediated HCC, develops chronic cholestatic hepatitis at an early age and HCC at an adult age. To delineate factors contributing to hepatocarcinogenesis, we compared the severity of early chronic hepatitis and late HCC development in two Mdr2‐KO strains: Friend virus B‐type/N (FVB) and C57 black 6 (B6). We demonstrated that hepatocarcinogenesis was significantly less efficient in the Mdr2‐KO/B6 mice versus the Mdr2‐KO/FVB mice; this difference was more prominent in males. Chronic hepatitis in the Mdr2‐KO/B6 males was more severe at 1 month of age but was less severe at 3 months of age in comparison with age‐matched Mdr2‐KO/FVB males. A comparative genome‐scale gene expression analysis of male livers of both strains at 3 months of age revealed both common and strain‐specific aberrantly expressed genes, including genes associated with the regulation of inflammation, the response to oxidative stress, and lipid metabolism. One of these regulators, galectin‐1 (Gal‐1), possesses both anti‐inflammatory and protumorigenic activities. To study its regulatory role in the liver, we transferred the Gal‐1–KO mutation (lectin galactoside‐binding soluble 1−/−) from the B6 strain to the FVB strain, and we demonstrated that endogenous Gal‐1 protected the liver against concanavalin A–induced hepatitis with the B6 genetic background but not the FVB genetic background. Conclusion: Decreased chronic hepatitis in Mdr2‐KO/B6 mice at the age of 3 months correlated with a significant retardation of liver tumor development in this strain versus the Mdr2‐KO/FVB strain. We found candidate factors that may determine strain‐specific differences in the course of chronic hepatitis and HCC development in the Mdr2‐KO model, including inefficient anti‐inflammatory activity of the endogenous lectin Gal‐1 in the FVB strain. (HEPATOLOGY 2013 )